2020
DOI: 10.1016/j.tranon.2020.100860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of cancer stem cell chemotherapeutic assay for recurrent ovarian cancer

Abstract: Introduction Disease recurrence and progression of ovarian cancer is common with the development of platinum-resistant or refractory disease. This is due in large part to the presence of chemo-resistant cancer stem cells (CSCs) that contribute to tumor propagation, maintenance, and treatment resistance. We developed a CSCs drug cytotoxicity assay (ChemoID) to identify the most effective chemotherapy treatment from a panel of FDA approved chemotherapies. Methods Ascites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The InDels present only in patients were checked for its functional annotation and the InDels that have functional impact on the encoded proteins, were then taken to the analysis. The list of mutations characteristic for leukemias and pre-leukemic states [ 19 , 20 , 21 , 22 ] are presented in Table 1 , while the list of all InDels detected in the patients’ malignant cells is given in the Supplementary Table S1 . Moreover, the information about the fusion genes expressed in patients’ blasts was read out from RNAseq data and presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The InDels present only in patients were checked for its functional annotation and the InDels that have functional impact on the encoded proteins, were then taken to the analysis. The list of mutations characteristic for leukemias and pre-leukemic states [ 19 , 20 , 21 , 22 ] are presented in Table 1 , while the list of all InDels detected in the patients’ malignant cells is given in the Supplementary Table S1 . Moreover, the information about the fusion genes expressed in patients’ blasts was read out from RNAseq data and presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous prospective clinical investigation, we observed that recurrent ovarian cancer patients treated with high-cell kill chemotherapy agents guided by the CSCs assay had an improvement in the median PFS corresponding to 5.4 months (3 rd relapse), 3.6 months (4 th relapse), and 3.9 months (5 th relapse) when compared to historical data [ 37 ]. Additionally, in our previous study we also observed that ovarian cancer patients identified as non-responders by the CSC drug response assay had 30 times the hazard of death compared to those women that were identified as responders with respective median survivals of 6 months vs. 13 months [ 37 ], which is in agreement with our current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials, many of which have been supported by the Gynecologic Oncology Group (GOG), have investigated chemotherapy drugs, regimens, and reductive surgery methods in search of effective strategies to prevent EOC recurrence [ 37 ]. The AURELIA, OCEANS, and GOG-0213 phase-3 randomized trials have evaluated the use of bevacizumab in combination with chemotherapy for recurrent platinum-resistant and –sensitive ovarian cancer [ 46 49 ] and discovered that the PFS of patients treated with bevacizumab/chemotherapy was significantly prolonged (6.8 months versus 3.4 months, p<0.001) compared to patients treated with chemotherapy alone [ 37 ]. The median overall survival of these patients was 16.6 months for the bevacizumab/chemotherapy combination vs. 13.3 months for chemotherapy alone; however, this was not statistically significant (p=0.174).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical management of patients would be positively impacted by the successful eradication of CSCs ( 78 ). The clinical importance of CSC has been demonstrated by the shorter time to cancer progression and higher overall survival rates in patients with chemotherapy-sensitive CSCs than without them ( 79 ).…”
Section: Us-mediated Targeting Of Ovarian Cancer Stem Cellsmentioning
confidence: 99%